CD2AP at the junction of nephropathy and Alzheimer’s disease - Milene Vandal; Mohsen Janmaleki; Isabel Rea; Colin Gunn; Sotaro Hirai; Jeff Biernaskie; Justin Chun; Grant Gordon; Andrey Shaw; Amir Sanati-Nezhad; Gerald Pfeffer; Frederic Calon; et al. (Molecular Neurodegeneration)
Abstract Polymorphisms in the gene encoding CD2-associated protein (CD2AP) are associated with an increased risk for developing Alzheimer’s disease (AD). Intriguingly, variants in the gene also cause a pattern of kidney injury termed focal segmental glomerulosclerosis. Recent studies have investigated the cell types and mechanisms by which CD2AP gene dosage contributes to the key pathological features of AD. This review summarizes the fundamental roles of CD2AP in mammalian cells and systems, discusses the novel pathogenic mechanisms focused on CD2AP in AD and highlights the necessity of incorporating biological sex in CD2AP research. Finally, the article draws important parallels between kidney and brain physiology based on vascular and molecular organization, links kidney disease to AD, and suggests the existence of a kidney-brain axis in AD centered on CD2AP.